The Effects of Mnemonic Instructions on Paired-Associate Learning - Handelman, Elaine H. (My University, 1966)
Different instructions for associating concrete nouns were given in a paired-associate learning situation. Material was varied to produce different types of interference against which to evaluate the effectiveness of the different instructions.
The major findings were: (1) Specific instructions for association produced fewer errors than no specific instructions on the first list a subject learned. (2) After the first list, only the instructions which asked the learner to produce a logical scene from the nouns produced fewer errors than non-specific instructions. (3) Specific instructions did not interact with material.
Little evidence was found that the significant instructional effects were due to the specific characteristics of the learners' mediations. These effects were more plausibly attributed to such general mechanisms as either giving the mediations during learning or having learning time occupied with irrelevant activity.
Keywords: mnemonic, instructions, paired-associate, learning, mechanisms